Prediction of Turn-Ends Based on Anticipation of Upcoming Words - Magyari, Lilla; de Ruiter, Jan P. (Frontiers in Psychology, 2012)
During conversation listeners have to perform several tasks simultaneously. They have to comprehend their interlocutor’s turn, while also having to prepare their own next turn. Moreover, a careful analysis of the timing of natural conversation reveals that next speakers also time their turns very precisely. This is possible only if listeners can predict accurately when the speaker’s turn is going to end. But how are people able to predict when a turn ends? We propose that people know when a turn ends, because they know how it ends. We conducted a gating study to examine if better turn-end predictions coincide with more accurate anticipation of the last words of a turn. We used turns from an earlier button-press experiment where people had to press a button exactly when a turn ended. We show that the proportion of correct guesses in our experiment is higher when a turn's end was estimated better in time in the button press experiment. When people were too late in their anticipation in the button press experiment, they also anticipated more words in our gating study. We conclude that people made predictions in advance about the upcoming content of a turn and use this prediction to estimate the duration of the turn. We suggest an economical model of turn-end anticipation that is based on anticipation of words and syntactic frames in comprehension.